Primary Thyroid Lymphoma: A Rare Case Report - Krishnan, Sripriya; Renuka, I V; Ramya, C H; ., Harshitha (Annals of Pathology and Laboratory Medicine, 2020)
Primary thyroid lymphoma (PTL) is a rare condition and accounts for 5% of all thyroid malignancies. They constitute less than 2 % of all lymphomas. Most PTL’s are non-Hodgkin's lymphomas. It is clinically essential to discriminate between primary or secondary lymphoma of the thyroid as the treatment and prognosis varies. It commonly occurs in women in their sixth and seventh decade. Primary thyroid lymphoma is quite curable without the need for extensive surgery if diagnosed early. We present such a case of a 60- year old female patient presenting with complaints of neck swelling with loss of appetite and dysphagia. Histopathological diagnosis confirmed Primary thyroid lymphoma of B cell origin which was confirmed by immunohistochemistry.